Kajian Pemanfaatan Limbah Faba (Fly Ash Dan Bottom Ash) Pada Konstruksi Lapisan Permukaan Jalan (Top Layer) - Vira Afrilla; Alfian Malik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Asphalt is one of the materials used in road construction, this material was chosen because it can produce flexible, safe and comfortable pavement. One of the functions of adding fillers is to minimize the use of asphalt base materials, where this filler has a significant effect because it functions as a cavity filler. The filler used is factory waste, namely fly ash and bottom ash. Fly ash is the residue from burning coal in power plants. Bottom Ash as well as fly ash is the result of burning coal, the ash that is produced when burning coal that settles. The purpose of this study was to determine the effect of using FABA waste (fly ash and bottom ash) on the quality of the road surface construction layer (top layer). The proportions of fly ash and bottom ash used are 2%, 4%, 6%, 8% and 10% of the total weight mixture of the mixture where each variation of fly ash is 55%: 45% bottom ash. Marshall characteristic test results show that the addition of fly ash and bottom ash to the AC-WC mixture can increase the value of stability and the of void filled with asphalt (VFA) and can reduce the value of void in the mixture (VIM) with certain filler levels according to the tests that have been carried out which can be used in the field, namely variation 2 %, 4%, 6% and 8%. The optimum variation of fly ash and bottom that can be added to AC-WC mixture 2% of the total aggregate weight. This value is based on the high stability value compared to other variations is 1654,74 kg. Keywords: AC-WC, Bottom Ash, Filler, Fly Ash, Top Layer.